Impact of Problem-Solving Coping Strategies on Occupational Stress among Hotel Workers in Pokhara - Thapa, Surya Bahadur Thapa (NPRC Journal of Multidisciplinary Research, 2026)
Background: The prevalence rate of occupational stress is high within the hospitality industry due to working for long hours, emotional pressures, and continuous interaction with clients. The problem-solving coping strategy serves as an important strategy that helps reduce stress among workers in such organizations. Research Purpose: This study seeks to examine the relationship between the problem-solving coping strategy and occupational stress among hotel workers in Pokhara. Methods: A quantitative survey research design was adopted. Data were collected from 250 employees working in 15 star-rated hotels in Pokhara using a structured questionnaire. The study employed purposive sampling for hotel selection and convenience sampling for respondents. Data were analyzed using SPSS-26 through descriptive statistics, Pearson correlation, and linear regression analysis. Findings: The findings indicate that employees experienced occupational stress at a high level 3.96 (SD = 0.57). Problem-solving coping was found to be negatively and significantly correlated with occupational stress (r = -0.421, p < 0.001). Problem-solving coping was found to significantly predict occupational stress through regression analysis (β = -0.421, R² = 0.178, p < 0.001). Conclusion: Problem-solving coping strategies play a significant role in reducing occupational stress among hotel employees in Pokhara. However, the relationship is associative, not causal. Novelty: This study contributes empirical evidence from Nepal’s hospitality sector, highlighting the importance of coping strategies in managing occupational stress.